2017
DOI: 10.1016/j.kint.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Applications of the CRISPR-Cas9 system in kidney research

Abstract: The recently discovered clustered regularly interspaced short palindromic repeat (CRISPR)-CRISPR-associated protein 9 (Cas9) is an RNA-guided DNA nuclease, and has been harnessed for the development of simple, efficient, and relatively inexpensive technologies to precisely manipulate the genomic information in virtually all cell types and organisms. The CRIPSR-Cas9 systems have already been effectively used to disrupt multiple genes simultaneously, create conditional alleles, and generate reporter proteins, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 123 publications
0
12
0
2
Order By: Relevance
“…CRISPR-Cas9 technology has been employed as a simple, efficient, and relatively inexpensive technology to precisely edit genes for various applications, including transcriptional regulation, epigenetic control, and chromosome translocation. 27 , 28 , 29 Recently, this editing system has been harnessed to correct disease genes in human embryo genomes. 30 , 31 , 32 By tethering the C terminus of the catalytically inactive dCas9 to three epigenetic suppressor domains, we found that the synthetic dCas9 epi-suppressor gRNAs induced significant decreases in the transcription activity of the GRN target gene promoter in Hep3B hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR-Cas9 technology has been employed as a simple, efficient, and relatively inexpensive technology to precisely edit genes for various applications, including transcriptional regulation, epigenetic control, and chromosome translocation. 27 , 28 , 29 Recently, this editing system has been harnessed to correct disease genes in human embryo genomes. 30 , 31 , 32 By tethering the C terminus of the catalytically inactive dCas9 to three epigenetic suppressor domains, we found that the synthetic dCas9 epi-suppressor gRNAs induced significant decreases in the transcription activity of the GRN target gene promoter in Hep3B hepatoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-guided Cas9 nuclease system has also become a powerful tool for both forward and reverse genetics (Gurumurthy et al, 2016c), generating models that are relevant for many diseases, including cancer (Platt et al, 2014). Several recent review articles discuss the Cas9-nuclease-generated mouse models for different disease types, including for cancer (Mou et al, 2015; Roper et al, 2017), cardiovascular diseases (Miano et al, 2016), neurodegenerative diseases (Yang et al, 2016) and kidney diseases (Higashijima et al, 2017). In addition, several reviews on Cas9-nuclease-generated models have been recently published that discuss their human disease relevance (Dow, 2015; Tschaharganeh et al, 2016; Cai et al, 2016; Yang et al, 2016; Birling et al, 2017).…”
Section: Programmable Endonucleases For Genome Editingmentioning
confidence: 99%
“…It was reported that the CRISPR/Cas9 system can be used for genome editing in mammalian cells. The following studies found that the CRISPR/ Cas9 system can be utilized to generate KO mice efficiently [18]. At this point, CRISPR/Cas9 ultimately came to the world as genetic engineering technology.…”
Section: Overview Of Crispr/cas9 Techniquementioning
confidence: 99%